Enabling Excellence in Contractor Safety Management: Elements to Generate Sustained Contractor Safety Performance in Oil & Gas - Bouadjel, Aissam (Digital Repository of Theses, 2025)
The Oil and Gas (O&G) industry relies heavily on contractors for specialized jobs, particularly high-risk activities such as Facilities Desing and Construction, Shutdowns and Turnarounds, Drilling and Well Servicing and many others. However, managing a diverse contractor workforce presents a lot of challenges that compromise safety, regulatory compliance, and operational efficiency which often results in a high fatality rate among contractors’ workers. This study aims to explore key drivers of excellence in Contractor Safety Management (CSM) and develop a systematic approach to improving CSM in the O&G industry. The research objectives included: (1) reviewing current industry practices in CSM, (2) assessing the effectiveness of existing CSM practices, and (3) designing a comprehensive model integrating key factors, best practices, regulatory requirements, and technological advancements. A mixed-methods research design was employed, combining both qualitative (document analysis and structured interviews) and quantitative methods (questionnaire surveys), PLS modeling and descriptive analysis were used for data analysis. The study revealed seven key elements for implementing and sustaining contractors’ safety performance in the Oil and Gas industry: (1) Joint leadership Commitment & Accountability, (2) Pre-qualification, (3) On boarding, Training and Competency Assurance (4) Effective Communication, (5) Effective Supervision, (6) Audits, Compliance Assurance, Performance Management, (7) Digitalization and Data Analytics, (8) Collaboration and Fair Treatment, (9) Risk based Management Approach, (10) Emergency Response and Incident Management. This, the study has several contributions: first, the study contributes to bridge the gaps arising from limited empirical studies regarding CSM in O&G. Second: The study contributes to the academic understanding of contractor safety management and its relationship with organizational performance and refines existing theories on safety culture and SMS by incorporating contractor-specific dynamics. Third, this will help both O&G Companies as well as Service Providers with developing comprehensive CSM Systems that effectively manages risks, enhances safety performance, fosters a culture of continuous improvement and sustainability, and helps policymakers in crafting regulations that better address the complexities of CSM in O&G Industry.